STORYTELLING – MARKETING OF THE FUTURE - Раменська, Світлана (SWorldJournal, 2023)
Every day, marketers are faced with the problem of creating demand through the use of various means of marketing communications. Effective impact on the end consumer in order to motivate him to the required action, i.e. to making at least a test purchase